2022
DOI: 10.1177/23779608221129936
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Disability Upgrading Among Leprosy Patients During Treatment: Multilevel Modeling Analysis

Abstract: Background Leprosy not only brings about bodily incapacity but also creates a nasty image of affected individuals, triggering discrimination and social stigma. The purpose of this study was to evaluate the status of leprosy disability in patients registered at the All African TB and Leprosy Rehabilitation and Training Center. Methods The study consists of 205 leprosy patients who were undergoing treatment at the All African TB and Leprosy Rehabilitation and Training Center from January 2015 to December 2019. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
(80 reference statements)
0
0
0
Order By: Relevance
“…Previous studies have shown the risk of disability was lower for patients whose lesion distribution is asymmetrical. 30 …”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown the risk of disability was lower for patients whose lesion distribution is asymmetrical. 30 …”
Section: Discussionmentioning
confidence: 99%
“…Mulugeta, SS et al (2022) 9 showed the distribution of disability among leprosy patients was not consistent across clusters. A two-level mixed-effects binary logistic regression model was used to analyze the effect of individual characteristics and community-level factors in determining disability among leprosy patients.…”
Section: Participantsmentioning
confidence: 99%